2019
DOI: 10.1080/19420862.2019.1596514
|View full text |Cite
|
Sign up to set email alerts
|

Sym021, a promising anti-PD1 clinical candidate antibody derived from a new chicken antibody discovery platform

Abstract: Discovery of therapeutic antibodies is a field of intense development, where immunization of rodents remains a major source of antibody candidates. However, high orthologue protein sequence homology between human and rodent species disfavors generation of antibodies against functionally conserved binding epitopes. Chickens are phylogenetically distant from mammals. Since chickens generate antibodies from a restricted set of germline genes, the possibility of adapting the Symplex antibody discovery platform to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 62 publications
0
26
0
1
Order By: Relevance
“…Although comparatively rare in humans, the presence of high cysteine numbers and motifs in CDR-H3s, as consistently observed in multiple individuals, is reminiscent of that found in chicken, camel, llama, shark, and cow. Knowledge of noncanonical cysteines and better understanding of their roles in creating genetic diversity and distinct paratope surfaces of these non-human species have led to the development of several promising antibody-discovery platform technologies (Feng et al, 2019;Gjetting et al, 2019;Kö nitzer et al, 2017;Muyldermans, 2013;Muyldermans and Smider, 2016). In contrast, for human, it was generally held that such genetic and structural diversity did not exist.…”
Section: Discussionmentioning
confidence: 99%
“…Although comparatively rare in humans, the presence of high cysteine numbers and motifs in CDR-H3s, as consistently observed in multiple individuals, is reminiscent of that found in chicken, camel, llama, shark, and cow. Knowledge of noncanonical cysteines and better understanding of their roles in creating genetic diversity and distinct paratope surfaces of these non-human species have led to the development of several promising antibody-discovery platform technologies (Feng et al, 2019;Gjetting et al, 2019;Kö nitzer et al, 2017;Muyldermans, 2013;Muyldermans and Smider, 2016). In contrast, for human, it was generally held that such genetic and structural diversity did not exist.…”
Section: Discussionmentioning
confidence: 99%
“…[16,17] In contrast, a recent publication reported the affinity for pembro to human PD-1 at 3.4 nM. [18] Discrepancies like this populate the biosensor literature, and make it difficult to compare published data, especially data where sensorgrams with fits are not shown. Since samples based on these and other INN-registered mAbs are often used as positive controls, we used these studies as an opportunity to thoroughly characterize their binding properties.…”
Section: Plos Onementioning
confidence: 99%
“…The PD-1 and PD-L1 sequence homologies were lower in chPD-1 and chPD-L1 sequences compared with those of the mammalian species (Jeon et al, 2007;Gjetting et al, 2019). The conservation of the ITIM and ITSM motifs in the C-terminal, and highly conserved TEYATIVF indicated that the immune signal regulation associated with PD-1 is highly conserved among species (Okazaki et al, 2001).…”
Section: Discussionmentioning
confidence: 94%